In silico assessment of coriander leaf extract active compound to resensitize oxaliplatin resistance in colorectal cancer mediated by ABCG2 and UPF1 proteins - Sun JESSICA; Sandra B. FILEMON; Sharron SANTOSA; Stephani C. MAHARANI; Arli A. PARIKESIT (Notulae Scientia Biologicae)
Colorectal cancer is, and continues to be, one of the most important global health burdens due to its notorious high mortality rate and continuous resilience to traditional modes of treatment, specifically chemotherapeutic agents such as oxaliplatin. The resistance is mediated through specified genes highly involved in survival and resistant mechanisms in cancerous cells, like ABCG2 and UPF1 genes. Given the challenge, this study focuses on the coriander leaf extract as a new strategy for overcoming oxaliplatin resistance in colorectal cancer. In the present study, the authors examined the anticancer activities of the extracts from coriander leaves, which exerted inhibitory activity toward ABCG2 and UPF1 proteins believed to be involved in chemoresistance. Molecular docking analysis was done by PyRx software to evaluate the binding properties of the target genes with the 31 compounds in coriander leaf extract to find the best compound that may give an efficient way of overcoming resistance against oxaliplatin. Out of all the compounds screened, rutin came out to be the potential candidate. The binding affinities were highly impressive, about -8.4 kcal/mol for UPF1 and -7.8 kcal/mol for ABCG2. These values are especially important because they exceed the conventional affinity of known chemotherapy inhibitors, such as Ko143 and actinomycin D, which served as positive controls in this study. The higher binding affinity of rutin indicates that it may potentiate chemotherapy by specifically targeting ABCG2 and UPF1 in colorectal cancer cells. This strategic approach could limit the resistance to oxaliplatin and increase the treatment success rate in colorectal cancer patients. The observations of this work open up new perspectives in the study of natural products as adjuvants or alternatives to traditional chemotherapy that, in the future, could give rise to more efficient and less toxic strategies against colorectal cancer.